2018
DOI: 10.1016/j.matchar.2018.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of isochronal annealing on the microstructure, texture and mechanical properties of a cold-rolled high manganese steel

Abstract: Effect of isochronal annealing on the microstructure, texture and mechanical Effect of isochronal annealing on the microstructure, texture and mechanical properties of a cold-rolled high manganese steel properties of a cold-rolled high manganese steel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Thus, the present investigation tracks the evolution of the microstructure and e-and a¢-martensite reversion mechanisms during the in situ annealing of an Fe-17Mn-3Al-2Si-1Ni-0.06C steel. Our previous ex situ annealing study of the same high Mn steel also showed the formation of twins in reverted c. [23] In the present follow-up in situ annealing work, the mechanism of twin formation in reverted c is explored.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Thus, the present investigation tracks the evolution of the microstructure and e-and a¢-martensite reversion mechanisms during the in situ annealing of an Fe-17Mn-3Al-2Si-1Ni-0.06C steel. Our previous ex situ annealing study of the same high Mn steel also showed the formation of twins in reverted c. [23] In the present follow-up in situ annealing work, the mechanism of twin formation in reverted c is explored.…”
mentioning
confidence: 73%
“…[22] Our previous ex situ annealing study of high Mn steel tracked the reversion of e-and a¢-martensite to c in multiple samples heated to different temperatures. [23] However, the e-and a¢-martensite reversion mechanisms can be better investigated via in situ annealing experiments. To our knowledge, the literature does not contain any in situ annealing studies of e-and a¢-martensite reversions in high Mn steels.…”
mentioning
confidence: 99%
“…The {001}<110> component showed high intensity, as indicated in Figure . In fact, the {001}<110> orientation is formed with ideal {001}<100> and {110}<112> orientations through the K‐S orientation . Weidner et al reported a similar orientation in high‐alloy metastable austenitic CrMnNi steel with different nickel contents for cold rolling of less than 70%.…”
Section: Discussionmentioning
confidence: 99%
“…To‐date, limited studies are conducted to elucidate the strain localization using DIC in phase transforming high Mn steels subjected to uniaxial tension . Although tensile testing was performed on a steel of similar composition, it was undertaken without DIC. Furthermore, the microstructural characterization via EBSD before and after tension was also missing.…”
Section: Introductionmentioning
confidence: 99%